2021
DOI: 10.21037/tlcr-21-885
|View full text |Cite
|
Sign up to set email alerts
|

BCKDK alters the metabolism of non-small cell lung cancer

Abstract: Background: Metabolic reprogramming is a major feature of many tumors including non-small cell lung cancer (NSCLC). Branched-chain α-keto acid dehydrogenase kinase (BCKDK) plays an important role in diabetes, obesity, and other diseases. However, the function of BCKDK in NSCLC is unclear. This study aimed to explore the function of BCKDK in NSCLC.Methods: Metabolites in the serum of patients with NSCLC and the supernatant of NSCLC cell cultures were detected using nuclear magnetic resonance (NMR) spectroscopy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…Consistent with the findings in terms of insulin resistance, the BCAA metabolism was also altered in various cancers ( vide supra ) ( 131 134 ). In a seminal article, Sivanand and Heiden reviewed the fundamental perspectives concerning the critical role of BCAA metabolism in cancer ( 143 ).…”
Section: Mtorc1 and Branched-chain Amino Acidssupporting
confidence: 85%
See 2 more Smart Citations
“…Consistent with the findings in terms of insulin resistance, the BCAA metabolism was also altered in various cancers ( vide supra ) ( 131 134 ). In a seminal article, Sivanand and Heiden reviewed the fundamental perspectives concerning the critical role of BCAA metabolism in cancer ( 143 ).…”
Section: Mtorc1 and Branched-chain Amino Acidssupporting
confidence: 85%
“…Several recent works highlighted the importance of the BCAA metabolism and BCKDK in cancers (131)(132)(133)(134)(135)(136)(137). It was shown that higher BCKDK expression was associated with shorter survival in colorectal cancer, and BCKDK could promote tumorigenesis in vivo and ex vivo through the mitogen-activated protein kinase (MAPK) signaling pathway (131).…”
Section: Catabolism Of Branched-chain Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation rate of BCKDH represents BCKDK function as well. At the same time, the function of BCKDK in glucose metabolism can be measured by the uptake amount of glucose, the production level of lactate, the oxygen consumption rate in the cell, the extracellular acidification rate, and reactive oxygen species ( 23 , 24 ).…”
Section: Detection Methods Of Branched-chain Amino Acids and Branched...mentioning
confidence: 99%
“…BCKDK expression is increased in high-grade ovarian cancer [ 27 ] and in chemotherapy-resistant disease [ 28 ]. In colorectal and non-small cell lung cancer, expression of BCKDK correlates with poor patient survival [ 12 , 29 ]. Apart from BCAA metabolism, BCKDK also regulates other cancer-relevant pathways through the direct phosphorylation of MEK [ 29 ] and ATP citrate lyase [ 30 ].…”
Section: Introductionmentioning
confidence: 99%